A new species of Erythrogonia Melichar, 1926 (Insecta: Hemiptera: Cicadellidae: Cicadellini) from the Mantiqueira mountain range, southeastern Brazil, associated with olive orchards - Froza, Joyce A.; Quintas, Victor; Mejdalani, Gabriel (Zootaxa, 2021)
A new species of the diverse Neotropical sharpshooter genus Erythrogonia Melichar, 1926 is described and illustrated from the Mantiqueira mountain range, municipality of Maria da Fé, state of Minas Gerais, southeastern Brazil. The new taxon is associated with olive orchards and has been implicated as a vector of the bacterium Xylella fastidiosa Wells et al., 1987, which causes a disease known in Brazil as olive leaf scorch syndrome. Erythrogonia sinvali sp. nov. can be distinguished from the other 90 known species of the genus by the following combination of features: (1) crown black without conspicuous contrasting spots; (2) frons with large yellow median spot; (3) pronotum black with large yellow area covering most of disk; (4) forewing dark red, without contrasting spots or stripes, costal margin narrowly black, apical portion dark brown; (5) aedeagus elongate, curved dorsally, with pair of spiniform apical processes; (6) paraphyses greatly reduced; (7) basal portion of male anal tube with pair of spiniform curved processes; (8) posterior margin of female abdominal sternite VII broadly emarginate and with broad central lobe; (9) female sternite VIII with sclerotized areas, including a transverse bar located at bases of ovipositor valvulae I, followed by a pair of elongate sclerites and a posterior bilobed sclerite. Both males and females of the new species are described in detail. A putative group of five species within Erythrogonia is preliminarily proposed, including the new taxon, E. separata Melichar, 1926, E. dorsalis (Signoret, 1853), E. calva (Taschenberg, 1884), and E. melichari Schmidt, 1928. Among these species, the male terminalia of E. sinvali sp. nov. are more similar to those of E. separata.